2017
DOI: 10.1103/physreva.95.033618
|View full text |Cite
|
Sign up to set email alerts
|

Landau criterion for an anisotropic Bose-Einstein condensate

Zeng-Qiang Yu

Abstract: In this work, we discuss the Landau's criterion for anisotropic superfluidity. To this end, we consider a point-like impurity moving in a uniform Bose-Einstein condensate with either interparticle dipole-dipole interaction or Raman induced spin-orbit coupling. In both cases, we find that the Landau critical velocity vc is generally smaller than the sound velocity in the moving direction. Beyond vc, the energy dissipation rate is explicitly calculated via a perturbation approach. In the plane-wave phase of a sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
2
11
0
1
Order By: Relevance
“…Thus, its contribution to the drag force (25) does not vanish. A similar suppression of the dissipationless motion has been found in the uniform plane-wave phase [44].…”
Section: Drag Force and Energy Dissipation In The Stripe Phasesupporting
confidence: 78%
See 2 more Smart Citations
“…Thus, its contribution to the drag force (25) does not vanish. A similar suppression of the dissipationless motion has been found in the uniform plane-wave phase [44].…”
Section: Drag Force and Energy Dissipation In The Stripe Phasesupporting
confidence: 78%
“…( 26) it follows that the critical speed v ℓ,c can depend on the direction v of the motion. This effect has already been addressed in several works [44][45][46][47], which focused on the uniform plane-wave and zero-momentum phases. It has also been found that the drag force can be not parallel to v, and the critical velocity can be different from the sound velocity even in the directions perpendicular to the condensation momentum.…”
Section: Drag Force and Energy Dissipation In The Stripe Phasementioning
confidence: 89%
See 1 more Smart Citation
“…The Landau criterion [2] then relates the anisotropy of the excitation spectrum to the breakdown of superfluidity, since quasiparticles cannot be emitted by an impurity moving at a velocity v smaller than the critical velocity v c = min[ ω(k)/k ] in an isotropic fluid. For anisotropic interactions the excitation wavevector k does not necessarily coincide with the direction of movementv of the impurity [13]. In its generalized form the Landau crite-rion therefore becomes v c = min[ ω(k)/(k ·v) ].…”
mentioning
confidence: 99%
“…Utilizando interação com lasers podemos proporcionar acoplamento entre as componentes do espinor que descrevem o condensado. Embora recentes, já acumula uma lista crescente de temas estudados da qual fazem parte solitons [13,14,15], estudo de vórtices [16], verificação experimental para 2 [17] ou os 3 [18], entre outros [19,20,21].…”
Section: Rudimentos Da Condensação De Bose-einstein E Estrutura Hiperunclassified